2019
DOI: 10.1016/j.jpainsymman.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Volunteer-Professional Collaboration in Palliative Care: A Qualitative Study Among Volunteers, Patients, Family Carers, and Health Care Professionals

Abstract: Context. Governments intend to meet resource constraints in professional palliative care by stimulating informal care, including volunteerism. However, little is known about current volunteer-professional collaboration. Such insights are relevant for future policy development regarding volunteer efficiency, quality of care, and the capacity of volunteer care to support health care services and professionals.Objectives.To explore what constitutes volunteer-professional collaboration around palliative care. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Lower response rates from certain types of volunteers, such as those in nursing homes and community home care, imply possible issues for statistical generalisation and, hence, that results for the particular organisational types should be interpreted with caution. Results nevertheless confirm the findings from a previous organisational study of palliative care volunteering (Vanderstichelen et al, ; Vanderstichelen, Houttekier, et al, ) and are contextualised by previous qualitative studies of volunteering in these settings (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, ; Vanderstichelen et al, ), indicating the validity of our current conclusions. Strongly involved volunteers may be overrepresented in these strata.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Lower response rates from certain types of volunteers, such as those in nursing homes and community home care, imply possible issues for statistical generalisation and, hence, that results for the particular organisational types should be interpreted with caution. Results nevertheless confirm the findings from a previous organisational study of palliative care volunteering (Vanderstichelen et al, ; Vanderstichelen, Houttekier, et al, ) and are contextualised by previous qualitative studies of volunteering in these settings (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, ; Vanderstichelen et al, ), indicating the validity of our current conclusions. Strongly involved volunteers may be overrepresented in these strata.…”
Section: Discussionsupporting
confidence: 91%
“…Across health services, volunteers collaborated mainly with fellow volunteers, volunteer coordinators, nurses and family caregivers. Dedicated palliative care volunteers collaborated most often and extensively with nurses, confirming previous studies that have shown the importance of nurses to palliative care volunteering (Vanderstichelen, Cohen, et al, ; Vanderstichelen et al, ). Inpatient care service volunteers collaborated more with nurses than extramural care volunteers, however, the latter collaborated more with family caregivers than other volunteers.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations